New technology trends and policy needs in energy efficient motor systems - A major opportunity for energy and carbon savings. (November 2019) - De Almeida, A.; Fong, J.; Brunner, C.U.; Werle, R.; Van Werkhoven, M.
Abstract: The electric motor market has witnessed a major change in the last decade in several aspects: in structure, with company mergers contributing to a more global market, in content with energy-efficiency policies, and in its economy due to increasing electricity prices, all aspects contributing to push the market towards more energy-efficient electric motors. Additionally, the growing market penetration of Variable Speed Drives (VSD), introducing large energy savings in systems with variable loads, was accompanied by a growing concern over their operating efficiency in full and especially in part-load, as well as in stand-by mode. A Motor Driven Unit (MDU) consists of the core components of a motor system: electric motor, variable speed drive (VSD), mechanical transmission and end-use application, like a pump or fan. Regulating the entire Motor Driven Unit (MDU) would translate into 1400 TWh of cost-effective electricity savings (7% of the World motor systems electricity consumption), with a corresponding reduction in emissions of 469 Mton of CO2eq by 2040. Even larger potential energy savings can be made available by the optimization of the entire motor systems, which translates into 3100 TWh of global electricity savings by 2040. Still to date, Minimum Energy Performance Standards (MEPS) have been mostly targeted at individual components only. Difficulties arise in the standardization of measuring and classifying the entire MDU but the larger energy savings achievable by the motor system is leading to the launch a combined system standard by the International Electrotechnical Committee (IEC) and the International Organization for Standardization (ISO). MEPS and standardization at the component and MDU level must be carefully complemented to achieve the maximum energy savings and carbon emission reductions. This paper carries out novel technical, economic and environmental analyses of introducing new policy measures (standards and MEPS) for both individual components and MDUs. Highlights: A review of international regulatory options for electric motors is given. An analysis of the environmental impacts and electricity consumption of motors and its improvement potential is made. A review of new technology developments in motors and drives is made. Impact on global electricity consumption and GHG emissions of introducing system energy efficiency regulation is estimated. Current standardisation status is analysed and challenges for future system approach are identified.